Introduction to Polyphasic Dispersed Systems Theory Application to Open Systems of Microorganisms' Culture - Thierie, Jacques; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book introduces a new paradigm in system description and modelling. The author shows the theoretical and practical successes of his approach, which involves replacing a traditional uniform description with a polyphasic description. This change of perspective reveals new fluxes that are cryptic in the classical description. Several case studies are given in this book, which is of interest of those working with biotechnology and green chemistry.
General Introduction -- General Results -- Continuous Cultures: The Chemostat -- General Discussion.
Keywords: Fluid mechanics; Soft condensed matter; Microbiology; Biotechnology; Engineering Fluid Dynamics; Soft and Granular Matter; Microbiology; Biotechnology